2021
DOI: 10.3389/fphy.2021.627826
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Control of the Optical Response of Aluminum Phthalocyanine Chloride Complexes Dissolved in Ethanol

Abstract: We show that absorption spectra of aluminum chloride phthalocyanine (AlClPc) in the liquid phase can be dynamically modified through the time-resolved interaction with a second laser pulse during a time window on the order of 100 fs. The observed effects can be explained by laser-induced coherent coupling dynamics between the ground state and a bath of excited states as reproduced by a few-level toy model. The presented results help to understand how intense laser fields interact with complex molecules in solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A number of femtosecond 4WM experiments revealed that richer information on the photoinduced dynamics in atomic vapors, polyatomic chromophores, multichromophore aggregates, and nanosystems can be obtained by applying more intense laser pulses (see refs for reviews). On the theoretical side, a variety of simulations of 4WM signals beyond the limit of weak system–field coupling have been reported. ,,,, Single-molecule femtosecond spectroscopy of individual chromophores and antenna complexes , also usually requires strong pulses.…”
Section: Nonperturbative Calculation Of the Nonlinear Polarizationmentioning
confidence: 99%
“…A number of femtosecond 4WM experiments revealed that richer information on the photoinduced dynamics in atomic vapors, polyatomic chromophores, multichromophore aggregates, and nanosystems can be obtained by applying more intense laser pulses (see refs for reviews). On the theoretical side, a variety of simulations of 4WM signals beyond the limit of weak system–field coupling have been reported. ,,,, Single-molecule femtosecond spectroscopy of individual chromophores and antenna complexes , also usually requires strong pulses.…”
Section: Nonperturbative Calculation Of the Nonlinear Polarizationmentioning
confidence: 99%